Understanding the chemical structure of carbon edge sites by using deuterium-labeled temperature-programmed desorption technique. (May 2020) - Ishii, Takafumi; Ozaki, Jun-ichi
Abstract: A deuterium-labeled temperature-programmed desorption (TPD) technique was developed to accurately characterize functional groups on the surface of carbon-based materials. After the protic hydrogen of the functional groups on activated carbons was substituted by deuterium, TPD analysis revealed the desorption of deuterium compounds (D2 O, DHO, D2, DH). The functional groups were estimated from the predicted desorption mechanisms of these deuterium compounds, which can be distinguished according to the functional groups and their surrounding chemical structures. Thus, this technique provides information on not only the type of functional groups but also the extensive chemical structure around them. The phenolic group, ether, and edge hydrogen formed on the activated carbons were separately quantified, and the functional groups were further classified into 12 types by the nearby chemical structures. Comparison with IR spectra indicated that the deuterium-labeled TPD gave qualitatively reasonable results. This technique is useful for obtaining a deeper understanding of the surface chemical structure of carbon-based materials. Graphical abstract: Image 1